Morphometrical Analysis of Suprarenal Gland in Fetuses of Different Gestational Ages - Mini Mol P.; Gautam Shroff; Sumi Elizebeth Reny (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
Background & Objectives: Suprarenal glands are a pair of glands situated on the posterior abdominal wall on each side of vertebral column. Over the past years, the evaluation of foetal morphometrical growth parameters have been a subject of increased awareness for the assessment of foetal growth and development. Brown and Singer stated that the size of glands were reduced in fetuses from unsuccessful pregnancies of patients with hypertension and in anencephalic fetus, adrenal age was below the normal range in fetuses with congenital adrenal hyperplasia. The suprarenal glands are recognizable with foetal MRI by 20 weeks of gestation and as early as 12th week of gestation by trans abdominal ultrasonography. Therefore, the knowledge of normal variation in weight, size, shape with gestational ages is of great significance. Methods: The study was performed on 110 supra renal glands of both right and left obtained from 55 aborted human fetuses between 9-36 weeks of gestational ages. The present study was carried out in the Department of Anatomy, MGM Medical College, Navi Mumbai and Aurangabad Morphological details of both supra renal glands were studied. The dimension weight, crown lump length the relative weight of right and left suprarenals studied and statistically analyzed. Results: The result indicates that, there is high significant increase in the body weight with increase in gestational age (P < 0.01) and also high significant increase in the crown rump length with increase in gestational age (P < 0.01). there is high significant increase in the crown rump length with increase in gestational age (P < 0.01). The result indicates that, there is high significant difference in the relative weight of right suprarenal with increase in gestational age (P < 0.01). Interpretation & conclusions: The knowledge of normal variation in weight, size ,shape with gestational ages is of great significance as these nomograms help us to control the state of a foetus in high risk pregnancies